Effect of Powder Sizes, pH of Water, Ultrasound and Method of Distillation on Extraction of Fennel Essential Oil and Anethole Content: Effect of some conditions on essential oil of fennel - Tavakolizadeh, Mahdi; Ghazaleh Hadian,; Khoshayand, Mohammad Reza; Faraz Mojab, (Iranian Journal of Pharmaceutical Sciences, 2018)
The essential oils are frequently used in food processing industry, perfumery, cosmetics, and pharmaceuticals. Most of the oils were obtained by steam distillation and water distillation. It is necessary to specify the best conditions of essential oils production to get much more major compound(s) and higher yield oil. So, fennel oil was selected in this study. The objective of this work was to identify the effect of powder’s particle size, pH of water, method of distillation and using ultrasound on extraction of fennel essential oil (and its major constituent, anethole). We used a statistical method called D-optimal Design that appointed pH, particle size, and method for each assay. First, the seeds powder distillated directly. In the second series, the seeds were placed in an ultrasonic apparatus for 30 minutes. The essential oils were subsequently isolated by two methods, hydro-distillation, and steam-distillation in different sizes and pH in Clevenger apparatus. Gas chromatography was used to determination of major component (E-anethole) in fennel essential oils. Finally, optimum conditions according to the statistical results are as follows: Method: steam distillation, and mesh size: 50. So it shows that steam distillation is more efficiently than water distillation.